Physiotherapeutic treatment in patients with heel spurs - Strojek, Katarzyna; Karpińska, Anna; Strączyńska, Agnieszka; Zukow, Walery; Radzimińska, Agnieszka (Journal of Education, Health and Sport, 2018)
The heel spur is a disorder resulting from biomechanical abnormalities of the foot. The problem affects people of different ages and arises as a result of repeated micro-injuries within the flexor digitorum brevis. The main reason for treating patients is pain. There are many conservative methods of treatment of heel spurs and related complaints resulting from inflammation of the plantar foot aponeurosis. The most effective include: kinesitherapy, physiotherapy, manual therapy and dynamic slicing. Available research indicate the effectiveness of the therapy with the use of: stretching exercises, ultrasounds, low and high-energy laser therapy, shockwave, vibroacoustics, relaxation of myofascial trigger points and therapeutic tapering.